Antagonistic interaction between zinc and cadmium in cocoa (Theobroma cacao L. var. CCN-51) seedlings amended with rock phosphate - Díaz Chuquizuta, Henry (2026)
Introduction: In the San Martın region, several studies have reported Cd concentrations in surface soils approaching the upper limit (UL), with mean values ranging from 0.27 to 1.351 mg·kg- ¹. Methods: Cadmium (Cd) transfer to Theobroma cacao (CCN-51) seedlings was evaluated under 12 factorial combinations of phosphate rock (RFP) and foliar zinc sulphate (ZnSO4) applications, using relative uptake (foliar Cd/soil Cd) as the primary response variable. Results: The treatment showing the highest Cd uptake was T4, defined as RFP = 0 mg·kg-1 and ZnSO4 = 527.80 mg·plant-1, with a value of 53.12. The observed range in relative uptake was 33.08 units, indicating substantial variation among management combinations. At the factor-level analysis, the high RFP treatment (114.55 mg·kg- ¹) was associated with an average reduction of approximately 26.5% in relative uptake and lower within-group variability compared to the 0 mg·kg- ¹ level. Interaction plots indicated that the effect of ZnSO4 on nutrient uptake depended on RFP level, with a descending response profile at high RFP concentrations. In parallel, soil correlation analyses identified available phosphorus and pH as the principal modulators of Cd transfer from soil to plant. Leaf-level principal component analysis showed that Zn and K were projected in the opposite direction to P2O5 and Cd, consistent with an ionic balance mechanism regulating Cd accumulation, and achieved an overall classification accuracy of approximately 81%, thereby confirming multivariate separability among treatments. Discussion: Collectively, these integrated results support identifying T4 as the treatment with the highest Cd uptake within the evaluated set. Accordingly, the presence of Zn²+–Cd²+ antagonism can be asserted; however, its expression is strongly influenced by soil pH and, most critically, by the availability of phosphorus derived from RFP.